Effectiveness of acupuncture for temporomandibular disorders and associated symptoms - Garbelotti,Thânia Orlando (2016)
ABSTRACT BACKGROUND AND OBJECTIVES: Temporomandibular disorder is defined as a set of clinical problems involving masticatory muscles, temporomandibular joint and associated structures. For having multifactorial etiology, several treatments are proposed and successfully used. However, most recommended therapies are those reversible and noninvasive, which should be the first choice to treat temporomandibular disorders. This study aimed at discussing acupuncture to treat temporomandibular disorders and associated symptoms. CONTENTS: This is a review of 34 articles published between 1983 and 2015. Since acupuncture aims at returning balance to body and harmony between physical and psychical parts by stimulating specific points, it may be considered therapy of choice to treat temporomandibular disorders. In TMD patients, evidences have shown efficacy in increasing temporomandibular joint movement amplitude, accelerating serotonin, encephalin and endorphin release, thus favoring masticatory muscles relaxation and pain relief. According to recent articles, most commonly used points for this purpose are: ST6, ST7, SJ21, SJ17, SI18, Taiyaing and Yintang (face and head) and LI4 (extrafacial). CONCLUSION: Acupuncture is as effective to control facial pain as conventional Western therapies. It is considered useful, of low cost and provides better quality of life to patients treated with this technique.